2011
DOI: 10.4049/jimmunol.1100007
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2/PTEN Pathway Plays a Key Role in Platelet-Activating Factor-Mediated Murine Anaphylactic Shock

Abstract: Platelet-activating factor (PAF) is a major mediator in the induction of fatal hypovolemic shock in murine anaphylaxis. This PAF-mediated effect has been reported to be associated with PI3K/Akt-dependent eNOS-derived NO. The phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is phosphatidylinositol phosphate phosphatase, which negatively controls PI3K by dephosphorylating the signaling lipid, phosphatidylinositol 3,4,5-triphosphate. In this study, we examined the possible involvement of PTEN in PAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Many signals, such as LPS, TNF‐ α , interleukin‐1, transforming growth factor‐ β and interferon‐ γ have been found to enhance the constitutive activity of CK2 . In the present study, we confirmed the results of our previous study, showing that PAF enhances CK2 activity . Additionally, we further demonstrated that PAF enhanced CK2 α phosphorylation and its protein expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many signals, such as LPS, TNF‐ α , interleukin‐1, transforming growth factor‐ β and interferon‐ γ have been found to enhance the constitutive activity of CK2 . In the present study, we confirmed the results of our previous study, showing that PAF enhances CK2 activity . Additionally, we further demonstrated that PAF enhanced CK2 α phosphorylation and its protein expression.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the molecular mechanism underlying the regulation of CK2, we have recently reported that PAF increases the enzymatic activity of CK2 in vivo . This suggests the possibility that CK2 is involved in biological roles of PAF.…”
Section: Introductionmentioning
confidence: 96%
“…Of note, increased E2F1 leads to p53-dependant repression of VE 40,41 , which normally destabilizes VE-cadherin junctions 19 , which may also contribute to this phenotype. This observation is supported by the fact that E2F1 knockout mice have increased vascular permeability, rapid PTEN reduction is seen during anaphylaxis, and that PTEN-deficient mice have enhanced allergic responses and increased vascular permeability 40,4244 . While the link between STAT3, the miR17–92 complex, PTEN expression and SRC-mediated responsiveness to histamine appears intriguing, further work will be necessary to definitively describe this mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…We showed that the decreased PTEN activity played a role in the tumor metastasis by demonstrating that systemic administration of Ad‐PTEN not only restored PAF‐induced reduction in PTEN activity but also inhibited PAF‐induced tumor metastasis. We previously showed that PAF induced decrease in PTEN activity plays a key role in the induction of anaphylaxis [29]. Therefore, PTEN involvement seems to be a central mechanism underlying the biological actions of PAF.…”
Section: Discussionmentioning
confidence: 95%